P150 Once-daily tiotropium Respimat® reduces risk of severe asthma exacerbation and asthma worsening in symptomatic asthma, independent of allergic and inflammatory status. (12th November 2015) - Dahl, R; Casale, T; Vandewalker, M; Schmidt, H; Engel, M; Moroni-Zentgraf, P; Kerstjens, HAM
Abstract : Background: Four trials explored whether tiotropium Respimat® add-on to at least ICS is effective in the TH 2 phenotype, determined by high serum immunoglobulin E (IgE) and blood eosinophil values, in reducing risk of severe asthma exacerbation and asthma worsening in adult patients with moderate or severe symptomatic asthma. Methods: Four Phase III, double-blind, placebo-controlled, parallel-group trials. PrimoTinA-asthma® (two 48-week trials; NCT00776984 /NCT00772538; n = 912): tiotropium Respimat® 5 µg or placebo Respimat® add-on to ICS + LABA (≥800 µg budesonide or equivalent); MezzoTinA-asthma® (two 24-week trials; NCT01172808 /NCT01172821; n = 2100): tiotropium Respimat® 5 µg, tiotropium Respimat® 2.5 µg or placebo add-on to ICS (400–800 µg budesonide or equivalent). Patients had symptomatic asthma requiring treatment with at least ICS for ≥4 weeks before screening; COPD was excluded. Subgroups of allergic and inflammatory status (IgE and eosinophils) were used to analyse risk of severe exacerbation and asthma worsening, post hoc . Cox regression modelling analyses, adjusted for treatment, IgE or eosinophils and treatment by IgE or eosinophil interaction, were applied to calculate hazard ratios and 95% confidence intervals across IgE (2–2000 μg/L) and eosinophil (0.05–7.00 × 10 9 /L) values. Results: Severe exacerbation: in PrimoTinA-asthma®, tiotropium Respimat® 5 µg reduced risk in terms of hazard ratio versus placebo Respimat® up to an IgE level of ~1000 µg/L, and consistently across all eosinophil values. In MezzoTinA-asthma®, tiotropium Respimat® 5 µg and 2.5 µg reduced risk versus placebo consistently across all IgE and eosinophil levels. Asthma worsening: in PrimoTinA-asthma®, tiotropium Respimat® 5 µg reduced risk in terms of hazard ratio versus placebo Respimat®, independent of IgE and eosinophils. In MezzoTinA-asthma®, tiotropium Respimat® 5 µg reduced risk versus placebo across all IgE and eosinophil values. Tiotropium Respimat® 2.5 µg reduced risk versus placebo across all IgE values and at eosinophil values <3.00×10 9 /L. Conclusion: Tiotropium Respimat® add-on to ICS ± LABA reduces risk of severe exacerbation and asthma worsening in patients across severities of symptomatic asthma and a broad range of IgE and eosinophil values, suggesting efficacy independent of underlying allergic/eosinophilic inflammation. Once-daily tiotropium Respimat® may have potential as add-on to at least ICS maintenance therapy in patients with symptomatic asthma, independent of TH 2 phenotype.